Comparing The Professional Commitment of Midwives from X and Y Generations - Mehtap Gümüşdaş; Merve Lazoğlu; Serap Ejder Apay (Association of Nurse Managers, 2021)
INTRODUCTION: Aim: This study was conducted to compare the professional commitment of the midwives from the X and Y generations. Method: This research with descriptive design was carried out among midwives in two cities in the Eastern Anatolia in September and November 2019. The study population consisted of the midwives from the X and Y generations, working in the relevant hospitals between the aforementioned dates, and agreed to participate in the study voluntarily. The data of the study were collected by 7-8 interviewers and researchers in each province. The data were collected using the Personal Information Form and the Midwifery Belonging Scale (MBS). Before collecting the study data, an ethics committee approval was obtained and once the midwives were informed, their verbal consent was obtained. Results: Based on comparison of the midwives' descriptive characteristics, it was determined that 42,9% of the midwives from the X generation and 81,2% of the midwives from the Y generation had a bachelor's degree. It was found that 8.4% of the midwives from the X generation and 82.7% of the midwives from the Y generation chose their profession willingly. It was determined that the mean scores of professional developments and opportunities subscale of the midwives from the X and Y generations who were included in the study were 18.61+-3.44 and 19.49+-3.72, respectively and the difference between them was statistically significant (p=0.006). It was determined that the mean scores of professional task and authority limitations subscale of the midwives from the X and Y generations were 10.90+-3.96 and 11.99+-3.31, respectively and the difference between them was statistically significant (p=0.001). It was found that the difference between the total mean score of the MBS was not statistically significant between the groups in the X and Y generations(p>0,05). Conclusion: According to the results of the research, it was observed that the sense of commitment was higher in the generation Y. METHODS: RESULTS: DISCUSSION AND CONCLUSION: